La expresión corporal en el proceso de aprendizaje en los niños de 4 a 5 años de la Unidad Educativa Aloasí en la Provincia de Pichincha, Cantón Mejía, Parroquia Aloasí en el año lectivo 2019-2020. - Tipán Guanochanga, Sandy Johanna (2020)
This research was carried out in the Unidad Educativa Aloasí, located in the Pichincha Province Canton Mejia, Aloasí Parish during the 2019-2020 school year, having as a study population children 4 to 5 years of level 2 preschool, in which it was possible to observe and demonstrate the difficulty in body expression and therefore in learning, so an alternative solution to the problem found in infants was proposed, this research was framed within a qualitative approach since it studies the reality of a natural context, with the case study method, based on observation, field, documentary bibliography, and in turn active techniques were carried out regarding surveys of parents, interviews to teachers of the Institution, observation sheets for children , these application instruments allowed to obtain positive results after their respective analysis and interpretation of results thus reaching the conclusion that body expression is significant to develop cognitive, motor, affective and social skills, to solve the problem, a guide to recreational activities will be developed with the Game-work methodology which will contribute to the development of new knowledge, It should be mentioned that teachers play a very important role in this process since they do everything possible for the child to explore, discover, know and interact with others, communicating and expressing feelings, thoughts and emotions using their body language as a expressive medium, helping to develop the ability to use your entire body.